A Comprehensive Review on the Latest Insights into Cold Therapies and Their Impact on the Human Body, with a Focus on Neurophysiological Responses - Karol Stachyrak; Anna Gregułą; Bartosz Mazur; Dawid Mika; Aleksandra Kłos; Kamila Turek; Maciej Lambach; Mateusz Pawlicki; Aleksandra Mazurek; Wiktoria Wilanowska (Kazimierz Wielki University, 2024)
Introduction             In contemporary medicine, increasing attention is being devoted to alternative forms of therapy. Immersing oneself in cold water, cryotherapy, or cold showers are practices that have long sparked interest due to their potential health benefits. Aim of the study             The aim of this comprehensive review is to analyze the impact of cold exposure on the human body, with particular emphasis on its effects on the nervous system. Through the synthesis of available research, the paper seeks to identify health benefits and areas requiring further investigation in the context of various cold application practices. Materials and methods             An analysis of scientific articles available in the Pubmed and Google Scholar databases was conducted. Publications from recent years that most relevantly addressed the discussed topic were utilized for this study. The search process involved the use of the following keywords: "cold," "cold showering," "cold water," "cryotherapy." Results             The results of the literature review unequivocally indicate a positive, multifaceted impact of cold on the human body, particularly with an emphasis on the nervous system. Significant therapeutic effects observed in various fields suggest that the application of cold may be a promising alternative in promoting health and treating numerous medical conditions. Summary             The focused literature review on the impact of cold on the human body, especially the nervous system, presents various therapies such as cryotherapy or cold water immersion, emphasizing their beneficial effects on the nervous, cardiovascular, endocrine, lymphatic, musculoskeletal, and joint systems. However, despite the observed benefits, further research is needed to gain a more detailed understanding of the mechanisms of action and to ensure the safety of these practices.